How to Achieve Efficient Land Use under Private Land Ownership - Overcoming a Global Obstacle Overlooked by Theodore W. Schultz and Albert O. Hirschman - Jian-Ming Zhou (European Regional Science Association (ERSA), 2003)
This paper challenges Nobel laureate Schultz's assertions: small farmers are rational; low income countries saddled with traditional agriculture have not the problem of many farmers leaving agriculture for nonfarm jobs; part-time farming is efficient; economies of scale do not exist in agriculture; and investment in human capital counts much more than institutions and is the key to agricultural growth. It reveals inefficient land use by able-bodied part-time/absent small farmers as an obstacle with both public and private land ownership, traditional and modern agriculture, low and high income economies, food under-self-sufficiency and overproduction, and developing and developed countries, albeit land property rights have been defined and sale/lease allowed, causing uneven regional development (e.g., in the enlarged EU after 2004), and other problems. Nobel nominees Hirschman overlooks this obstacle has made the linkages unfunctionable, while Cheung ignores clear definition of property rights is not sufficient to realize property transfer for more efficient use. It has been overcome by China under public land ownership, but not under private one in Europe, Asia, Africa, and Americas. Although a legislation to oblige landowners to either cultivate land or lease it for farming is implemented in Norway because of under-self-sufficiency, it ceased in the EU due to a dilemma: obliging landowners to do so would cause overproduction; otherwise, much land would be used inefficiently, then how to achieve economies of scale, reduce costs and compete with other countries' Without a solution, the EU turned to protect farmers by high subsidies and tariffs, making them less competitive, and harming other countries. Thus the EU correctly proposed in 2002 to decouple subsidies from production, which, however, could not bypass this dilemma. Once the USA has followed the EU, it would also meet it. This legislation has not been popularized to many other countries with under-self-sufficiency, because it obliges landowners to lease out ALL the inefficiently used land, so that part-time/absent landowners could not keep farming skills; and once lost off-farm jobs, would either have no access to the land rented out, or have to withdraw it, affecting the lessees. The paper invents a legislation to oblige farmers to either cultivate land or lease a part for farming, at under-self-sufficiency stage; or to grant right to full-time farmers to lease in a part of the inefficiently used land, at overproduction stage [i.e., a farmer is not obliged to either cultivate land or lease it for farming actively; but if another farmer wants to lease in a part of his inefficiently used land for farming, he is obliged to agree passively; subsidies (decoupled from production) and tariffs should be reduced to the WTO standards to prevent incentive for overproduction]. The landowners may keep a part of land for self-consumption, forming a Dual-Land System, so that their rural habitation could be reserved, farming skills kept, and small farmers not squeezed from agriculture; while the land for market is leased to full-time farmers to achieve economies of scale and reduce costs. It has obtained appreciation by the EU, OECD and World Bank. (500 words)
Keywords: 330